Antagonistic rhizoplane bacteria and their effects on the symbiosis between Trifolium repens L. and Rhizobium trifolii Dangeard - Hattingh, M. J.(Marthinus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (DSc) -- University of Stellenbosch, 1968.